Cerebroprotective activity of 3-benzylxanthine derivative – compound Ale-15, in conditions of bilateral common carotid arteries ligation (ischemic stroke) - Levich, Sergey V.; Aleksandrova, Katherine V.; Belenichev, Igor F.; Shkoda, Alexander S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Acute ischemic stroke is a leading cause of mortality, morbidity, long-term disability in industrialized countries. One of main parts of it pathogenesis is production of reactive oxygen species. The accumulation of them in neurons results in lipid peroxidation, protein oxidation, DNA damage, and finally cell death. Thereby the search of novel drugs, that have antioxidant action and can be used to complex treatment of cerebral strokes is reasonable. It is known, that xanthine derivatives exhibit a broad spectrum of biological activity, including antioxidant. So that, the goal of this research was to study in vivo neuroprotective action of water-soluble derivative of 3-benzylxanthine – morpholin-4-ium 3-benzylxanthinyl-8-methylthioacetate (Ale-15 compound) in comparison with neuroprotector-antioxidant – Mexidol. Methods: Experimental part was done on white Wistar rats of both sexes of 220-260 g weight. For assessment of neuroprotective action of compound we used a model of global incomplete cerebral ischemia, that was reproduced by bilateral common carotid arteries ligation. Results: It was studied an acute toxicity of Ale-15 compound, it influence on survival of laboratory animals, on progression of neuralgic deficit, on the content of adenylic nucleotides, on criteria of energy metabolism, on the activity of antioxidant enzymes and on oxidative modification of protein. Results of study showed, that injection of Ale-15 compound to animals with ischemic stroke intragastrically during 4 days positively reduced death rate and quantity of animals with serious neurologic symptoms. The main parts of Ale-15 cerebroprotective mechanism are antioxidant and anti-ischemic actions. Conclusions: The performed study revealed significant cerebroprotective features of Ale-15 compound in conditions of experimental cerebrovascular accident.